2015
DOI: 10.1016/j.physletb.2015.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Faddeev–Popov method for a deformed supersymmetric Yang–Mills theory

Abstract: In this paper, we will study the deformation of a three dimensional N = 2 supersymmetry gauge theory. We will deform this theory by imposing non-anticommutativity. This will break the supersymmetry of the theory from N = 2 supersymmetry to N = 1 supersymmetry. We will address the problem that occurs in the Landau gauge due to the existence of multiple solutions to the gauge fixing condition. This will be done by generalizing the Faddeev-Popov method. This formalism is motivated from the Nicolai map in topologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In our earlier works [11][12][13][14][15][16][17], we have shown that any arbitrary Abelian p-form (p = 1, 2, 3) gauge theory in D = 2p dimensions of spacetime within the framework of BRST formalism and the N = 2 SUSY quantum mechanical models, turn out to be the tractable model for Hodge theory. It would be interesting to implement this idea in the case of a free particle system on a toric geometry [40], supersymmetric Yang-Mills [24,[41][42][43]. Furthermore, the derivation of proper (anti-)BRST symmetries with the help of superfield formalism would be a nice piece of work in the context of deformed super-Yang-Mills, supersymmetric Chern-Simons, ABJM and BLG theories [43][44][45].…”
Section: Off-shell Nilpotent (Anti-)brst Symmetry Transformations And...mentioning
confidence: 99%
“…In our earlier works [11][12][13][14][15][16][17], we have shown that any arbitrary Abelian p-form (p = 1, 2, 3) gauge theory in D = 2p dimensions of spacetime within the framework of BRST formalism and the N = 2 SUSY quantum mechanical models, turn out to be the tractable model for Hodge theory. It would be interesting to implement this idea in the case of a free particle system on a toric geometry [40], supersymmetric Yang-Mills [24,[41][42][43]. Furthermore, the derivation of proper (anti-)BRST symmetries with the help of superfield formalism would be a nice piece of work in the context of deformed super-Yang-Mills, supersymmetric Chern-Simons, ABJM and BLG theories [43][44][45].…”
Section: Off-shell Nilpotent (Anti-)brst Symmetry Transformations And...mentioning
confidence: 99%